Object oriented data analysis - Marron, James Stephen, 1954-; Dryden, I. L. (Ian L.) ([Boca Raton] : Taylor & Francis Group, LLC, 2021)
"Object Oriented Data Analysis (OODA) provides a useful general framework for the consideration of many types of Complex Data. It is deliberately intended to be particularly useful in the analysis of data in complicated situations which are typically not easily represented as an unconstrained matrix of numbers"--
What is OODA? -- Breadth of OODA -- Data object definition -- exploratory and confirmatory analyses -- OODA P -- Data visualization -- Distance based methods -- Manifold data analysis -- FDA Curve Registration -- Graph structured data objects -- Classification -- supervised learning -- Clustering -- unsupervised learning -- High dimensional inference -- High dimensional asymptotics -- Smoothing and SiZer -- Robust methods -- PCA details and variants -- OODA context and related areas.
OCLC-licensed vendor bibliographic record.
Keywords: Object-oriented methods (Computer science); Quantitative research; Statistics -- Methodology; COMPUTERS / Computer Graphics / General; MATHEMATICS / Probability & Statistics / General